Rationally Designed Silicon Nanostructures as Anode Material for Lithium‐Ion Batteries. Issue 1 (5th October 2017) - Shen, Tong; Yao, Zhujun; Xia, Xinhui; Wang, Xiuli; Gu, Changdong; Tu, Jiangping
Abstract : Silicon (Si) is promising for high capacity anodes in lithium‐ion batteries due to its high theoretical capacity, low working potential, and natural abundance. However, there are two main drawbacks that impede its further practical applications. One is the huge volume expansion generating during lithiation and delithiation progresses, which leads to severe structural pulverization and subsequently rapid capacity fading of the electrode. The other is the relatively low intrinsic electronic conductivity, therefore, seriously impacting the rate performance. In the past decades, numerous efforts have been devoted for improving the cycling stability and rate capability by rational designs of different nanostructures of Si materials and incorporations with some conductive agents. In this review, the authors summarize the exciting recent research works and focus on not only the synthesis techniques, but also the composition strategies of silicon nanostructures. The advantages and disadvantages of the nanostructures as well as the perspective of this research field are also discussed. We aim to give some reference for engineering application on Si anodes in lithium ion batteries. Abstract : The authors summarize the strategies that developed lately for improving the electrochemical performance of Si materials. Special focus in this review is the recent progresses in the rational fabrication of Si nanostructures with multiple morphologies, including nanoparticles, nanowires, thin films, and porous structures. Moreover, further improvement tactics, such as collaborating with carbonaceous materials, conductive polymers, and alloy materials are also discussed.